2014
DOI: 10.1007/s00586-014-3602-6
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted magnetic resonance imaging for the diagnosis of patients with lumbar nerve root entrapment syndromes: results from a pilot study

Abstract: For the first time, we have established data for the DRG and DSN in human lumbosacral spinal nerves (L1-S1), using diffusion-weighted magnetic resonance imaging techniques. 3 T ADC maps have a higher signal to noise ratio, thus offering better image quality. Results from this study suggest that DWI has added value as new diagnostic tools for patients with symptomatic lumbar nerve root entrapment syndromes as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Studies have found that ADC is significantly higher in compressed nerve roots than in contralateral uncompressed nerve roots. [ 18 20 ] However, other studies have found that the ADC value of compressed nerve roots is similar to that of normal nerve roots in LDH patients. [ 9 , 10 ] The present study found that in compressed nerve roots, the ADC value before surgery was significantly higher than that after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that ADC is significantly higher in compressed nerve roots than in contralateral uncompressed nerve roots. [ 18 20 ] However, other studies have found that the ADC value of compressed nerve roots is similar to that of normal nerve roots in LDH patients. [ 9 , 10 ] The present study found that in compressed nerve roots, the ADC value before surgery was significantly higher than that after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…DWIs and ADC maps of spinal nerve roots, ganglions, and nerves with generation of tractography [ 13 , 14 ] were shown to add value for the preoperative assessment of spinal nerve root lesions [ 15 , 16 ]. However, ADC values from the dorsal root ganglion in symptomatic patients were found to be inconsistent, but correlate with recovery from pain and numbness [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe that further larger study is warranted to determine the specificity and sensitivity of ADC maps for the assessment of radicular symptoms and nerve root compression. Sagittal ADC maps were used in this study for the nerve root assessment, while previous studies used axial ADC maps [ 15 , 16 ]. Axial ADC maps may be easier to identify nerve roots, but weather the quantitative ADC measurements from the axial and sagittal scans are different remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…22 The DWI technique promises a noninvasive diagnostic assessment of early changes associated with degenerative compression of spinal nerves. 23 Our patient presented with acute low back pain, and the diagnosis was CLDCS. No surgery was indicated because of the minimal neurologic findings.…”
Section: Discussionmentioning
confidence: 78%